Learning Management Berbasis Web : Efek pada Proses dan Hasil Belajar - Istiqomah Nugraheni (Universitas Pendidikan Mandalika, 2021)
The purpose of this research is to improve the process and student learning outcomes through the implementation of Web-based learning management. This research method using descriptive method. The subjects in this study were 30 students of SMP Negeri 27 Surakarta. Data collection techniques using interviews and observations. While the data analysis technique used quantitative and qualitative descriptive analysis. The results showed that at the preliminary study stage, the teacher observed student characteristics and learning conditions to determine appropriate activities. At the implementation stage, the teacher designs the lesson plan, determines learning resources, and carries out Web-based learning activities. At the evaluation stage, the teacher analyzes the increase in student learning outcomes with the impact of Web-based informatics learning outcomes that have been able to improve student learning outcomes.